Effects of deep breathing exercise on pulmonary function, perceived stress and physical fitness among healthy smokers - Tallyia Naz; Bakhtawar Aslam; Farwa Abid; Sidra Sabir (The Rehabilitation Journal, 2025)
Background: smoking cessation is the most effective strategy to reduce smoking-related health risks, not all smokers are ready or able to quit immediately given the known benefits of deep breathing exercises on lung function, stress reduction, and physical fitness.